Association of Risk Factors for Uterine Cancer with Degree of Aggressiveness in Patients from Amazonia - Edison Enrique Sotalin Nivela; Jhonny Alejandro Rodríguez Gutiérrez; Eduardo Leonel Alvarado Pico (Medisur)
Foundation: cervical cancer emerges as a relevant concern, given its high incidence and impact on women's health, on a global scale. In recent years, in Ecuador, there has been an increase in new cases of cervical cancer. Objective: identify the relationship between some risk factors for cervical cancer according to the degrees of aggressiveness. Method: an observational, analytical and cross-sectional study was carried out. The population was made up of 224 patients from a hospital in the Amazon region of Ecuador. To identify the relationship between the variables age and body mass index, the analysis of variance test was used, while the X2 test was used for the variables: family history and smoking. Results: 3 patients with grade 1 of cervical cancer; 97 patients with grade 2 and 124 with grade 3, were identified. 62,05 % were 35 years old or older, 69,64 % of the patients were overweight or obese, 49,11 % had a family history of cervical cancer and 51,34 %, smoking. An association was found between the degree of aggressiveness of cervical cancer and body mass index (F = 3,440; p = 0,034), family history of cervical cancer (X2 = 10,618; p < 0,005) and smoking (X2 = 18,109; p < 0,001). Conclusions: a higher incidence of cervical cancer was found in women over 35 years of age. Factors such as body mass index, family history of cervical cancer and smoking showed a relationship with the grade of cancer.